Healthcare associated infection: good practices, knowledge and the locus of control in heatlhcare professionals - Taffurelli, Chiara; Sollami, Alfonso; Camera, Carmen; Federa, Francesca; Grandi, Annise; Marino, Marcella; Marrosu, Tiziano; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim. The incidence of Healthcare Associated Infections (HAI) is an important indicator of the quality of care. The behaviors associated with the prevention of infections are not only supported by rational knowledge or motivation, but are mediated by social, emotional and often stereotyped behaviors. The awarness of the good practices related to HAI, may be a factor. Other studies, identify how the perception of the problem in healthcare professionals is often influenced by a tendency towards an external Locus of Control: the patient, the family, the other wards, other care settings. The aim of this study is to investigate the perception of healthcare professionals. In particular they have been measured their awarness of the good practices, perceptions of the potential contamination level of some commonly used objects, knowledge about the management of invasive devices, Locus of Control. Method. A cross-sectional correlational design was utilized. An ad hoc questionnaire was interviewed by 222 health professionals nurses and physicians in a northern hospital of Italy. Results. The percentage of professionals who have attended training courses over the last 5 years was quite high, both for upgrades on HAI (78.7%) and Vascular Catheters (78.8%), while the percentage of professionals who updated on bladder catheterization (59.46%) was lower. The mean score of good practice awareness towards HAI (5.06), is high. The perception of the potential level of contamination of some devices had a mean ranging from 4.62 (for the drip) to 5.26 (for the door handle). The average value of the Locus of Control (43.54) indicates that participants demonstrated a value that is midway between External and Internal. The correlation test analysis revealed no significant relationships among professionals’age, knowledge about HAI, or infection related venus catheter. Also, results revealed that there were statistically significant positive relationships between professionals’ Good Practices awareness about HAI , Knowledge, and Locus of Control. Conclusion. The study findings demonstrated that good practice awareness towards HAI among nurse and physician was good but not completely optimal. Findings revealed that knowledge toward HAI prevention and HAI related device prevention were not completely adequate. The educational courses, according to our correlational findings, should definitely take into account the psycho-social aspects of this phenomenon.